Seasonal Variations in Trace Metals contamination in two species belonging to fish families Sciaenidae and Haemulidae from the Arabian Sea, Pakistan - Raza, Rashid (Journal of Research (Science), 2025)
Heavy metals contamination in food commodities is a serious threat because of their toxicity, bio-magnification and bioaccumulation in food chain, which has been increasing day by day. In the current study, heavy metal (Cd, Co, Cu, Pb and Ni) analysis was carried out in two different species Parastematus Gibosus, belonging to Heamulidae family and Johnnies Dussumieri belonging to Sciaenidae Family. These species were collected from two different locations i.e. West Wharf and Korangi Creek during Jan to December 2020. For fish samples of Sciaenidae, the concentration of Cd was observed to be 0.21 to 0.40μg g-1, Co was 16.5 to 18.6μg g-1, Cu was 15.2 to 23.5μg g-1, Pb was 4.1 to 9.2μg g-1 and Ni was22.5 to 35.3μg g-1. On the other hand, for fish samples of Haemulidae the concentration of Cd found as 0.17 to 0.38μg g-1, Co as 15.4 to 17.5μg g-1, Cu as 14.2 to 17.8μg g-1, Pb as 1.5 to 7.5μg g-1 and Ni as 23.5 to 34.8μg g-1. Cd and Pb was found highest in March, Cu in June, Ni in September and Co in December. Month-wise variation in heavy metals (Cd, Cr, Mn, Ni and Pb in the edible tissues of Parastematus Gibosus) for two different coastal areas i.e. Korangi Creek and West Wharf was also studied. For coastal area West Wharf, the concentration of Cr in the edible tissues of Parastematus Gibosusranged from 0.543 to 0.835μg g-1, Cd was 0.35 to 0.80μg g-1, Mn was 0.151 to 0.189μg g-1, Pb was 0.10 to 0.89μg g-1 and Ni was0.601 to 0.723μg g-1. On the other hand, for Korangi Creek the concentration of Cr was detected as 0.559 to 0.899μgg-1, Cd was 0.13 to 0.80μg g-1, Mn as 0.158 to 0.168μg g-1, Pbas 0.10 to 0.86μg g-1 and Ni as 0.664 to 0.712μg g-1.The results showed a significant difference of seasonal variation of heavy metals concentration in fish samples analyzed. The contamination in fish was higher during the summer season and lowest in winter season, therefore it is advisable to decrease the consumption of fish in summer to avoid the accumulation of heavy metals in human body.